Effect of date (Phoenix dactylifera L.) pit flour as alternative feed ingredients on egg quality of laying hens - Tasya Nur Karina; Osfar Sjofjan; Tri Eko Susilorini; Muhammad Halim Natsir (Universitas Sebelas Maret, 2022)
Objective: The aims this study of evaluate the effect of use date (Phoenix dactylifera L.) pits as alternative feed ingredient on egg quality of laying hens.Methods: This study was designed to consist of 5 treatments and 5 replications using a Completely Randomized Design (CRD) and if the effect was significant (P>0.05) or very significant (P>0.01), then Duncan's Multiple Distance Test (DMRT) was continued. The treatment in this research was the use of date pit flour with different concentration levels, namely 0% (P0), 2.5% (P1), 5% (P2), 7.5% (P3), and 10% (P4).Results: The results showed that the use of date pit flour could increase egg weight, shell weight, shape index, and yolk color.Conclusions: The use of date pit flour (Phoenix dactylifera L.) up to 10% level was used to improve the egg quality of laying hens.